Oxidative Stress Biomarkers and Left Ventricular Hypertrophy in Children with Chronic Kidney Disease - Drożdż, Dorota (Oxid Med Cell Longev, 2016)
Cardiovascular diseases remain the most frequent cause of morbidity and mortality in patients with chronic kidney disease (CKD). The aim of the study was to assess the association between oxidative stress biomarkers and cardiovascular risk factors and left ventricular hypertrophy in children with CKD. Material and Methods. The studied group consisted of 65 patients aged 1.4–18.6 (mean 11.2) years with stages 1 to 5 CKD. Serum oxidized low-density lipoprotein (oxLDL), protein carbonyl group, creatinine, cystatin C, albumin, lipids, high-sensitivity C-reactive protein, intercellular adhesion molecule-1, insulin, plasma renin activity, and aldosterone levels were measured. Patients were divided into groups depending on CKD stage. Anthropometric measurements, ambulatory blood pressure (BP) measurements, and echocardiography with left ventricular mass (LVM) calculation were performed. Results. Serum oxLDL strongly correlated with creatinine (R = 0.246; p = 0.048), cystatin C (R = 0.346; p = 0.006), total cholesterol (R = 0.500; p < 0.001), triglycerides (R = 0.524; p < 0.001), low-density lipoprotein concentrations (R = 0.456; p < 0.001), and 24 hour BP values of systolic (R = 0.492; p = 0.002), diastolic (R = 0.515; p < 0.001), and mean arterial pressure (R = 0.537; p < 0.001). A significant correlation between oxLDL levels and LVM z-scores (R = 0.299; p = 0.016) was found. Conclusions. Hypertension and dyslipidemia correlated with lipid oxidation in children with CKD. oxLDLs seem to be valuable markers of oxidative stress in CKD patients, correlating with left ventricular hypertrophy.